Evaluasi Program Pendidikan Karakter di Kelompok Bermain dan Taman Kanak-Kanak Candle Tree dengan Metode Context, Input, Process, dan Product (CIPP) [Evaluation of the Character Education Program in Candle Tree Playgroups and Kindergartens using the Context, Input, Process and Product (CIPP) Method] - Alvina, Bella (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2023)
It is crucial to instill character values from an early age to nurture a morally noble future generation. One way to achieve this is through a character education program. The purpose of this study is to evaluate the character education program carried out by Candle Tree Kindergarten since 2018/2019, with the aim of improving, enhancing, and perfecting it. This evaluation adopts the CIPP method, an acronym for Context, Input, Process, and Product. Qualitative and descriptive quantitative methods are employed to comprehensively analyze the evaluation results. Data collection methods used include questionnaires, interviews, observation, and documentation. To interpret various perspectives, different sources were consulted, and triangulation of sources was applied. The results of this study showed the following evaluation findings: a) Context: The program has the potential and capability to be implemented, but the program objectives were integrated into the school’s vision and mission. b) Input: Attention is needed for the program curriculum, budgeting, and variety of methods. c) Process: Improvement is needed for virtual interaction, medium of instruction, assessment guides, frequency, and program documentation. d) Product: Program results align with the characters instilled and trigger other values. Therefore, it can be concluded that this evaluation can be useful for the management of KB-TK Candle Tree to further develop character education programs.